2019
DOI: 10.3233/cbm-190414
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Apo10 and TKTL1: Epitope-detection in monocytes (EDIM) as a new diagnostic approach for cholangiocellular, pancreatic and colorectal carcinoma

Abstract: OBJECTIVE: The EDIM (Epitope detection in monocytes) blood test is based on two biomarkers Apo10 and TKTL1. Apo10 is responsible for cell proliferation and resistance to apoptosis. TKTL1 plays a major role in anaerobic glycolysis of tumor cells, leading to destruction of the basal membrane and metastasis as well as in controlling cell cycle. For the first time we analyzed Apo10 and TKLT1 in patients with cholangiocellular (CCC), pancreatic (PC), and colorectal carcinoma (CRC). METHODS: Blood samples of 62 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…In a previous study, TKTL1 could be detected using the epitope detection in monocytes (EDIM) blood test in all 34 pancreatic cancer patients studied, whereas a healthy control group exhibited a negative EDIM TKTL1 score [30]. Circulating TKTL1 is, however, not specific to pancreatic cancer, but also accompanies colorectal and biliary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, TKTL1 could be detected using the epitope detection in monocytes (EDIM) blood test in all 34 pancreatic cancer patients studied, whereas a healthy control group exhibited a negative EDIM TKTL1 score [30]. Circulating TKTL1 is, however, not specific to pancreatic cancer, but also accompanies colorectal and biliary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Like CTCs, CAMLs are detectable in patients with advanced cancers, but have low sensitivity for detecting disease in early stages [ 82 , 84 ]. Similarly, epitope-detection in monocyte (EDIM) technologies measure circulating CD14 + /CD16 + activated monocytes/macrophages with internalized tumor-derived proteins such as Apo10 and transketolase-like protein 1 (TKTL1) [ 88 , 89 ]. Such circulating cells are highly prevalent in oral cancer, PDAC, CRC, and cholangiocarcinoma, and reflect Apo10 and TKTL1 expression in primary tumors [ 88 , 89 ].…”
Section: Tumor-associated Macrophages Phagocytosis and Cancer-associa...mentioning
confidence: 99%
“…Similarly, epitope-detection in monocyte (EDIM) technologies measure circulating CD14 + /CD16 + activated monocytes/macrophages with internalized tumor-derived proteins such as Apo10 and transketolase-like protein 1 (TKTL1) [ 88 , 89 ]. Such circulating cells are highly prevalent in oral cancer, PDAC, CRC, and cholangiocarcinoma, and reflect Apo10 and TKTL1 expression in primary tumors [ 88 , 89 ]. Due to definitional and measurement differences, it is difficult to assess whether cells detected by EDIM platforms are CAMLs, as phagocytosis is just one method by which circulating cells in cancer can reflect tumor characteristics, such as cell death associated with treatment response.…”
Section: Tumor-associated Macrophages Phagocytosis and Cancer-associa...mentioning
confidence: 99%
“…These monocytes phagocytize tumor cells and store tumor proteins intracellularly. They can be detected in samples from peripheral blood of the patients using specific antibodies [ 12 ]. Particularly, the EDIM blood test focuses on the detection of two biomarkers, TKTL1 (transketolase-like protein 1) and Apo10 (epitope of DNaseX overexpressed in cancer cells), in CD14 + /CD16 + activated monocytes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Apo10 is highly expressed in neoplastic cells, including in carcinomas, sarcomas, glioblastomas, lymphomas, and leukemias [ 7 , 10 ]. In contrast, absent or only weak expression has been observed in hematopoietic cells [ 12 , 23 ].…”
Section: Introductionmentioning
confidence: 99%